Crossing borders and linking plural knowledge : biodiversity conservation, ecosystem services and human well-being - Alves, Fátima (2014)
The challenges we face today in terms of local, regional and global environmental changes and pressures on biodiversity can only be addressed with a close coupling of approaches from natural and social sciences together with local knowledge. The authors emphasise that biodiversity research and intervention should integrate this new comprehensive perspective, bringing together biological sciences, social sciences and local knowledge. This approach should demystify the traditional dichotomies that still impose epistemological and moral reductionist borders between nature and culture,systematically hiding the heuristic value of the social and cultural dimension of biodiversity loss. In this context, biodiversity is a field dominated by multiple tensions between plural knowledge within science itself and local knowledge (less visible), which brings to the discussion conflicts that are inherent to science, technology, economics, sociology, politics and culture. This is a fundamental dimension to understand and respond to the challenges we are facing on biodiversity loss.